Hypothyroidism masquerading as polymyositis. Issue 683 (September 1982) - Cabili, Shaltiel; Kaplinsky, Naomi; Pines, Amos; Frankl, Otto
Abstract : A group of patients is described who presented with proximal muscle weakness and elevated muscle enzymes. They were initially believed to have polymyositis and one of them was even treated as such over a long period of time. The patients were subsequently found to have hypothyroidism and responded well to thyroid hormone replacement. Hypothyroidism should always be considered in the differential diagnosis of polymyositis. A polymyositis-like picture has to be regarded as a symptom and not as a disease since it occurs in several metabolic, infectious, malignant and drug-induced diseases.